Association of Metformin Use and Survival Outcome in Women With Cervical Cancer. Issue 7 (1st September 2017) - Takiuchi, Tsuyoshi; Machida, Hiroko; Hom, Marianne S.; Mostofizadeh, Sayedamin; Frimer, Marina; Brunette, Laurie L.; Matsuo, Koji
Abstract : Objective: Although preclinical studies suggest possible antitumor effects of metformin against cervical cancer, there is currently a lack of clinical data examining the association of metformin use and survival in women with cervical cancer. The aim of this study was to examine survival of women with cervical cancer who were receiving metformin. Methods: This is a retrospective study examining consecutive cases of stages I to IV cervical cancer between 2000 and 2014. Patient demographics, medication use, tumor characteristics, treatment patterns, and survival outcomes were correlated to metformin use. Results: There were 70 (8.9%; 95% confidence interval [CI], 6.9–10.9) metformin users and 715 nonusers identified for the analysis. Median follow-up time was 22.6 months. Recurrence/progression of disease and death due to cervical cancer were observed in 236 and 163 cases, respectively. Metformin users were more likely to be older, hypertensive, diabetic, and dyslipidemic compared with nonusers (all, P < 0.05). On univariate analysis, metformin users and nonusers had similar progression-free survival (PFS) (5-year rates; 57.3% vs 61.8%; P = 0.82) and cervical cancer–specific overall survival (71.7% vs 70.7%; P = 0.86). After adjusting for patient demographics and tumor characteristics, metformin use was not associated with PFS (adjusted hazards ratio, 1.11; 95% CI, 0.70–1.74; P = 0.67) or cervical cancer–specific overall survival (adjusted hazards ratio, 0.91; 95% CI, 0.52–1.60; P = 0.75). Among 478 women who received whole pelvic radiotherapy, metformin use was not associated with PFS ( P = 0.93) or cervical cancer–specific overall survival ( P = 0.32). Conclusions: In this study population, metformin use was not associated with survival of women with cervical cancer.